A Study on Thermo-Viscous Steady Fluid Motion through a Moving Rectangular Flat Plate – A Numerical Approach - Pothanna, N.; Shekar, P. Raja; Cherukuri, Jyotsna; Rao, L. Srinivasa; Raju, Adigoppula; Suresh, Devunuri (East European Journal of Physics, 2026)
This study presents a novel numerical approach for analysis on thermo-viscous steady fluid motion over the moving rectangular permeable objects . The numerical results have been found employing Runge-Kutta method of order 6 shooting techniques developed in Mathematica software Numerical differentiation(ND) solve for the flow adaptable equations comprising temperature and velocity. The flow behavior and the impacts of material constraints on the flow region for governed equations of airflow around the aircrafts wings have been analyzed and deliberated taking the help from the generated graphs. The nonlinear coupled Partial differential equations(PDE’s) in terms of temperature and velocity, subject to the corresponding boundary conditions, control the fluid motion. The numerical computations of Runge-Kutta(R-K) 6th order results are presented in form of tables and also represented for numerous thermo physical coefficient values. The variations of these flow fields have been studied for wide spectrum of physical characteristics which influences the nature of thermo-viscous fluid. The impact of suction/injection parameter, dimensionless viscosity factor, constant pressure and temperature gradients, thermo physical factors and the Prandtl parameter effect on flow region have explored using graphical illustrations with the wide range of values. The Explicit numerical calculations also been calculated and results are associated through the current outcomes in the literature. To improve heat transfer rates in systems such as heat exchangers and aerospace components, engineers can optimize surface textures and flow conditions by taking coefficients effects on flow considerations into account.